Microsatellite (RM20A, RM241, and RM315) Amplification of Panic Grass DNA (Panicum maximum) - Gananto, Adrian Ramadhan; Islami, Romi Zamhir; Mansyur, Mansyur; Pramudyawardani, Estria Furry (Program Studi Peternakan, Fakultas Pertanian, Sains dan Kesehatan, Universitas Timor, 2024)
Forage is a very important element for livestock development as they need it to survive, produce and reproduce. The forages that is often used is panic grass (Panicum maximum) which is a feed grass from the African plains, widely used in various regions of Indonesia. This grass is used for their high nutritional value, the ability to adapt various types of soil and weather, and usage as an ideal or high quality “cut and carry” grass for beef and dairy cattle. Forage cultivation by considering plant genetics can improve the quality of all types of forage inherited from the parent hence increase the productivity of feed crops and support livestock development. This can be done with molecular marker, which is a technology that can confirm target genes effectively, efficiently and accurately and are not influenced by environmental factors. Among the markers or molecular markers currently available, microsatellites or Simple Sequence Repeats (SSR) have become a marker system that is commonly used because of its various advantages, namely that it can be amplified by Polymerase Chain Reaction using primers that combine sequences in the target DNA. In this research, genes that carry leaf-rolling, plant height, and fertility-restoring properties that have previously been identified in rice plants will be tested on panic grass using RM20A, RM241, RM315. After being visualized using electrophoresis gel, it can be concluded that RM241 had the best result as it has clear amplification result and polymorphic bands with effectiveness and polymorphism levels of 75% and 100% respectively.